In vivo evaluation of an antibacterial coating containing halogenated furanone compound-loaded poly(L-lactic acid) nanoparticles on microarc-oxidized titanium implants - Cheng Y (Dove Medical Press, 2016)
Yicheng Cheng,1–3,* Bo Gao,1,3,* Xianghui Liu,2,* Xianghui Zhao,4 Weige Sun,2 Huifang Ren,1,3 Jiang Wu1,3 1Department of Prosthodontics, State Key Laboratory of Military Stomatology, School of Stomatology, Fourth Military Medical University, Xi’an, 2Department of Stomatology, Bayi Hospital, Nanjing University of Chinese Medicine, Nanjing, 3Department of Prosthodontics, Shaanxi Key Laboratory of Stomatology, Xi’an, 4Institute of Neuroscience, School of Basical Medical Science, Fourth Military Medical University, Xi’an, People’s Republic of China *These authors contributed equally to this work Abstract: To prevent peri-implant infection, a new antibacterial coating containing a halogenated furanone compound, (Z-)-4-bromo-5-(bromomethylene)-2(5H)-furanone-loaded poly(l-lactic acid) nanoparticles, has been fabricated. The current study was designed to evaluate the preventive effect of the antibacterial coating under a simulated environment of peri-implant infection in vivo. Microarc-oxidized titanium implants treated with minocycline hydrochloride ointment were used as positive control group, and microarc-oxidized titanium implants without any treatment were used as blank control group. Three kinds of implants were implanted in dogs’ mandibles, and the peri-implant infection was simulated by silk ligation and feeding high sugar diet. After 2-month implantation, the results showed that no significant differences were detected between the experimental and positive control groups (P>0.05), but the data of clinical measurements of the blank control group were significantly higher than those of the other two groups (P<0.05), and the bone–implant contact rate and ultimate interfacial strength were significantly lower than those of the other two groups (P<0.05). Scanning electron microscope observation and histological examination showed that more new bone was formed on the surface of the experimental and positive control groups. It can be concluded that the antibacterial coating fabricated on implants has remarkable preventive effect on peri-implant infection at the early stage. Keywords: antibacterial coating, halogenated furanone, microarc-oxidized, nanoparticles, in vivo